Elucidation of some aspects of the physiological status of students and formation of skills to assess their own physiological condition in order to promote a healthy lifestyle - COȘCODAN, Diana; MOȘANU–ȘUPAC, Lora (Acta et Commentationes Exact and Natural Sciences, 2020)
The article elucidates the cardiovascular system status and stress levels of high school students. It addresses the research in biology class. The findings suggest the overexertion and fatigue of the cardiovascular system in children.